TEACHING PRACTICE AS A SETTING IN THE CONFIGURATION OF SUBJECTIVITIES AND KNOWLEDGE PRACTICES - Cristina Mónica Monti (Universidad Nacional del Nordeste, 2022)
This work tries to contribute different ways of thinking and ways of doing in the field of the formation of the teaching practices that are played in the curricular development of the Practice and Residence in Educational Institutions chair and its relationship with the curricular structure of the career to the which belongs: The Faculty of Educational Sciences. The field of teaching practices is intersubjective, where the heterogeneity and legitimacy of the differences between the interlocutors is recognized. The practitioner from his psychosocial structure interacts in a social network that contains and conditions him to a certain extent. Histories, formations and experiences depend on the set of interests based on which they take positions in relation to each other. The chair, in this sense, aspires to become a transversal space, for the construction of subjectivities and integration and articulation between theory and practice, for the creation of new imaginaries and meanings in pedagogical practices. Training thus constitutes a space to rethink the curricular path and teaching practice in particular. The perspective from which the work is proposed is located in the field of pedagogy of training from a complex perspective. In this perspective, professional training is an itinerary in which the practitioners, rather than respond to what the teachers indicate, is a journey that they must do by themselves: build theory and make the meaning of educational practice emerge.